Vegetable oil/styrene thermoset copolymers with shape memory behavior and damping capacity - Meiorin, Cintia (2012)
The mechanical and damping properties as well as the shape memory behavior of copolymers obtained by cationic copolymerization of tung oil with styrene with different stoichiometric ratios are presented and analyzed in this work. The glass transition temperatures are close to room temperature for all the copolymers, and generally increase with the content of styrene. A similar trend is observed for the modulus, which exhibits values from 4.89 MPa for the copolymer with 30 wt% styrene to 13.92 MPa for the copolymer with 70 wt% styrene. These hard elastomers present shape memory behavior with high recovery and fixity ratios, as well as high damping quality (damping factors 0.4 and 1.38 at 28.9 and 43.3 °C, for the tung oil homopolymer and the copolymer with 70 wt% styrene, respectively), opening possibilities for practical applications that require material response close to room temperature.